Risks of Hemorrhage and Poor Clinical Outcome in SLE with Thrombocytopenia at Dr. Sardjito Hospital - Surawijaya Bakhtiar Kaslam; Umi Solekhah Intansari (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease that affects various body organs and causes chronic inflammation. Thrombocytopenia is common in SLE, and there is a risk of causing bleeding, which can result in death. This study aimed to analyze the relationship of thrombocytopenia with bleeding and poor clinical outcomes in SLE patients at Dr. Sardjito Hospital. The design of this study was retrospective observational analytic. The research subjects were patients diagnosed with SLE at Dr. Sardjito Hospital from January 2016-December 2019 who conducted ANA and anti-dsDNA examinations. Statistical analysis using MedCalc version 13.0. Receiver operating characteristic curve analysis to determine the cut-off value of the platelet count for the occurrence of bleeding. Chi-Square for trend test to determine the relationship between the degree of thrombocytopenia and the degree of bleeding. Kaplan-Meier test to determine the six months survival analysis for SLE patients. There were 61 SLE patients at Dr. Sardjito Hospital. Thirty-two patients (52.5%) had thrombocytopenia. The AUC of the platelet count for the occurrence of hemorrhage was 0.988 (95% CI=0.918-1, p < 0.0001), the cut-off value was 146x103/L, sensitivity 100%, specificity 90.6%, and LR+ 10.33. The AUC of the platelet count for grade 3 hemorrhage was 0.929 (95% CI=0.833-0.979, p < 0.0001), cut-off value 91x103/L, sensitivity 100%, specificity 89.3%, and LR+ 9.33. Hemorrhage was seen in 29 subjects with thrombocytopenia. Five subjects (8.2%) died, with a significant difference in the mortality of SLE patients with and without thrombocytopenia in the six months survival analysis (p=0.028). The risk of hemorrhage and poor clinical outcome (death) were significantly higher in SLE patients with thrombocytopenia and increased with the thrombocytopenia grade.